Efektivitas Inovasi “One Day Service” Dalam Penerbitan Akta Kelahiran di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Tabanan - Felisa Rizky Amalia (Public Inspiration: Jurnal Administrasi Publik, 2021)
The “ONE DAY SERVICE” innovation is an innovation to accelerate the birth certificate in collaboration with hospitals within a one-day publishing speed. The “ONE DAY SERVICE” innovation is an effort made Office of Civil Registry and Population, Tabanan Regency's in increasing the coverage of birth certificate ownership at the age of 0-18 years in Tabanan District which is relatively low. The “ONE DAY SERVICE” innovation collaborates with three hospitals in Tabanan Regency including the Kasih Ibu Tabanan Hospital, Cahaya Bunda Mother and Child Hospital and the Tabanan Regional General Hospital. Problem in this study is How Effectiveness of “ONE DAY SERVICE” Innovation in the Population and Civil Registry Office of Tabanan Regency? and What are the supporting and inhibiting factors of “ONE DAY SERVICE” innovation in the Tabanan Regency Population and Civil Registry Office?. This study using 8 variable of effectiveness scale theory according to S.P Siagian and distructive innovation theory according to Clayton M. Christensen and Joseph Bower. This research method using qualitative method with descriptive design .